2020
DOI: 10.1021/acs.joc.0c01516
|View full text |Cite
|
Sign up to set email alerts
|

Trithiocarbonate Anion as a Sulfur Source for the Synthesis of 2,5-Disubstituted Thiophenes and 2-Substituted Benzo[b]thiophenes

Abstract: The trithiocarbonate anion (CS 3 2− ) was generated in situ from CS 2 and KOH in dimethyl sulfoxide by a simple method and used as a novel synthetic equivalent of the S 2− synthon for the synthesis of 2,5-disubstituted thiophenes from 1,3butadiynes. Additionally, this system was employed for the metal-free synthesis of 2-substituted benzo[b]thiophenes from 2haloalkynyl (hetero)arenes. These compounds were obtained from a cheap and readily available sulfur source in moderate to good yields, with good functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 120 publications
0
40
0
Order By: Relevance
“…Subsequently, we conducted experiments where a 1,3-diyne was added to the thioesterification in order to obtain evidence of the fragmentation of S 8 during photocatalysis. Previous reports have shown that anionic sulfur species such as hydrosulfides, S 3 radical anions, and trithiocarbonate anions can couple with 1,4-diphenyl-1,3-butadiyne 25 to provide a 1,4-diphenylthiophene 26 . , We obtained thiophene 28 in 91% yield following the reaction of 1,3-diyne 25 under the optimal conditions in conjunction with the complete cessation of the thioesterification reaction and full recovery of α-ketoacid 2 (Scheme B, eq 4). Moreover, we found that the use of diphenyltetrasulfide 27 ( E 1/2 = −0.53 V vs SCE) instead of S 8 also afforded thioester 3 and a similar inhibition of the thioesterification as seen in eq 4 was observed (eq 5).…”
mentioning
confidence: 89%
“…Subsequently, we conducted experiments where a 1,3-diyne was added to the thioesterification in order to obtain evidence of the fragmentation of S 8 during photocatalysis. Previous reports have shown that anionic sulfur species such as hydrosulfides, S 3 radical anions, and trithiocarbonate anions can couple with 1,4-diphenyl-1,3-butadiyne 25 to provide a 1,4-diphenylthiophene 26 . , We obtained thiophene 28 in 91% yield following the reaction of 1,3-diyne 25 under the optimal conditions in conjunction with the complete cessation of the thioesterification reaction and full recovery of α-ketoacid 2 (Scheme B, eq 4). Moreover, we found that the use of diphenyltetrasulfide 27 ( E 1/2 = −0.53 V vs SCE) instead of S 8 also afforded thioester 3 and a similar inhibition of the thioesterification as seen in eq 4 was observed (eq 5).…”
mentioning
confidence: 89%
“…The water bath needs to be refilled with room temperature deionized water every 12−18 h. With the above setup, the reaction temperature can be maintained at 21−23 °C within the water bath during the reaction for us. Substrates 1a-1b, [2] 1d-1f, [2] and 4a-4c [3] are known compounds in the literature. Products 3a, 3b [2] , 3e-3i [4] , and 3l are known compounds in the literature.…”
Section: General Remarksmentioning
confidence: 99%
“…Following the reported procedure: . [3] In a N2 glove box, the substrate terminal alkyne S3 (1.0 eq. ), CuI (1.0 eq.…”
Section: General Procedures For Synthesis Of Dialkyne Substratementioning
confidence: 99%
See 1 more Smart Citation
“…In this sense and aiming our continuous interest in the synthesis of chalcogen compounds, the present study describes a novel methodology involving in situ reduction of elemental selenium to generate a nucleophilic Se 2– species in superbasic media [KOH and dimethylsulfoxide (DMSO)] to produce 2,5-disubstituted photoactive selenophenes. The scope of the methodology was investigated using 1,3-diyne derivatives containing different substituents with electron-donating and electron-withdrawing features in different positions to verify electronic and steric effects.…”
Section: Introductionmentioning
confidence: 99%